KORELASI ANTARA KEPADATAN HUNIAN RUMAH DAN INSIDEN PNEUMONIA BERAT PADA ANAK BALITA DI WILAYAH KERJA PIMPINAN DAERAH ‘AISYIYAH KOTA PADANG - Melda Saputri; Mandria Yundelfa; Jeki Refialdinata; Nurhaida; Nova Rita; Meta Rikandi (Jurnal Keperawatan Abdurrab, 2026)
Pneumonia is a major cause of morbidity and mortality in children under five, especially in developing countries. Environmental factors, including overcrowding, play a significant role in increasing the risk of transmission. Houses with overcrowding of more than three people per room are likely to have poor air circulation, high humidity, and exposure to indoor pollution, which can accelerate the transmission of pneumonia-causing pathogens. This study aims to analyze the correlation between overcrowding and the incidence of severe pneumonia in children under five in the working area of ​​the Regional Leadership of ‘Aisyiyah, Padang City. This study is a quantitative study using a cross-sectional design. The study was conducted in the working area of ​​the Regional Leadership of ‘Aisyiyah, Padang City, with a sample of 58 parents with children under five years of age. Data collection was carried out using a questionnaire. The collected data were analyzed statistically. The results showed that the majority of respondents (69.0%) lived in overcrowded homes, and 72.4% of toddlers experienced severe pneumonia. The Chi-Square test showed no significant relationship between overcrowding and severe pneumonia (p=0.209). Health workers need to increase education regarding environmental health and early detection of pneumonia.